Ciência na praça: a divulgação científica e tecnológica na Amazônia - FERREIRA, Igor do Nascimento (2023)
This work aims to present the project Science in the Square, its operation, its objectives and the results obtained. The purpose is to prepare and expose diverse experiments, lectures and workshops, in a didactic and playful way, in several areas of knowledge such as: physics, biology, astronomy, engineering, medicine and others. The project targets the communities of the capital and the interior of the state of Pará, especially the young students of basic education in public education networks. In its five years of existence, more than twenty localities of the interior of the state were visited. We note, at each event, that the objectives of the project are being achieved, given that the public is increasing with each edition, in addition to the visibility that the latter has been gaining from the administrative bodies and educational institutions of the visited places.